Dimensions and levels of linguistic analysis - Dilfuza Sadilloevna, Fayazova; Mavlyuda Anvarovna, Mustafoyeva; Furqat Fattoxovich, Djalolov; Barat Baxronovich, Navruzov (International Journal of Psychosocial Rehabilitation, 2020)
There are a number of ideas on this matter: some linguists state that there are four units, such as phoneme-phone, morpheme-morph, lexeme-lex, and sentence; others believe that there are five units, like phonemes, morphemes, lexemes, word-combinations or phrases, and sentences. Yet others emphasized that in addition to the mentioned ones, there are paragraphs, utterances, and texts. As one can see, there's no unity in the number of language and speech units. The most well-known opinion is that there are five units of language (speech), and correspondingly there are five language levels; they are phonetic/phonological, morphological, lexicological, syntax-minor, and syntax-major. In this article, dimensions and levels of linguistic analysis are proved and outlined by the authors.